Stories of the States; a reference guide to the fifty States and the U.S. territories - Ross, Frank, 1914-1998 (Crowell, 1969)
A brief introduction to the history, geography, and resources of each state, territory, and trust of the United States. Charts give such factual information as state bird, song, motto, population, and nickname.